Revisiting the Y-3 tephrostratigraphic marker: a new diagnostic glass geochemistry, age estimate, and details on its climatostratigraphical context - TOMLINSON, EMMA (My University, 2015)
The ‘Y-3’ tephra is a crucial stratigraphic marker within the central Mediterranean region that falls close to the Marine Isotope Stage 3/2 transition and a cooling event proposed as a correlative of the North Atlantic Heinrich Stadial 3 (HS3). Consequently, this tephra offers great potential to assess any leads and lags in environmental responses to this abrupt climatic transition. New grain-specific glass analysis (EMPA and LA-ICP-MS) of the type locality Y-3 tephra recorded in the Ionian Sea confirms its origin from Campi Flegrei (CF) but reveals that it is compositionally different from the previously suggested proximal equivalent the VRa eruptive unit (Verdolino Valley, CF). Consequently, the 40Ar/39Ar age of the VRa should not be exported distally to the Y-3 tephra. Instead, we propose a new robust age for the Y-3 tephra following its identification in the Tenaghi Philippon sedimentary record, NE Greece. A Bayesian-based 14C age model from Tenaghi Philippon provides a distal age of 28,680–29,420 cal yrs BP for the Y-3 tephra. The identification of this tephra in NE Greece markedly extends its known eastern dispersal. Whilst its stratigraphic position falls within the latter part of a period of low tree pollen percentages related to dry stadial conditions. This new age and environmental context suggest that this marker postdates the onset of HS3 in the eastern Mediterranean region by ∼2300 years.
PUBLISHED
Keywords: Y-3 tephra; Ionian Sea; Mediterranean tephrochronology; Tenaghi Philippon; Stadial conditions; Bayesian age modelling; Smart & Sustainable Planet